Prognostic potential of the MDM2 309T>G polymorphism in stage I lung adenocarcinoma. (26th May 2016) - Enokida, Yasuaki; Shimizu, Kimihiro; Atsumi, Jun; Kakegawa, Seiichi; Takase, Yoshiaki; Kaira, Kyoichi; Yashima, Hideaki; Araki, Takuya; Nakazawa, Seshiru; Ohtaki, Yoichi; Nagashima, Toshiteru; Alexander, Lezhava; et al.
Abstract: The MDM2 protein plays an important role in the regulation of cell proliferation and apoptosis via ubiquitination and proteasome‐mediated degradation of p53. The genetic polymorphism rs2279744 (c.309T>G) of the MDM2 gene is reportedly associated with susceptibility and/or prognosis in various cancers. In this study, we investigated the risk factors for worse survival in patients with lung adenocarcinoma (AC). We examined the association between c.309T>G and the prognosis of lung cancer by retrospectively reviewing 453 lung cancer patients. We studied both, clinicopathological and genetic characteristics, including the c.309T>G, p53 Arg72Pro, EGFR, KRAS, and p53 mutations. Associations between these factors and survival outcome were analyzed using Cox proportional hazards models. The frequencies of MDM2 polymorphisms were T/T, 20.8%; T/G, 48.6%, and G/G, 30.7%. The overall survival (OS) of AC patients with pathological stage I disease and the MDM2 T/T genotype was significantly shorter than that of those with the T/G or G/G genotypes ( P = 0.02). Multivariate analysis revealed that the MDM2 T/T genotype was an independent, significant prognostic factor (hazard ratio [HR] = 2.23; 95% confidence interval [CI]: 1.07–4.65; P  =   0.03). The MDM2 T/T genotype was predictive of poorer survival in a Japanese population. Genotyping for this polymorphism might predict the clinical outcomes of stage I AC patients. Abstract : We examined the association between the c.309T>G polymorphisms of the MDM2 gene and lung cancer prognosis in 453 lung cancer patients. The MDM2 T/T genotype was an independent, significant prognostic factor (hazard ratio [HR] = 2.23; 95% confidence interval [CI]: 1.07–4.65; P  = 0.03) for pathological stage I adenocarcinoma patients.